The Role of Cytokines in Predicting the Response and Adverse Events Related to Immune Checkpoint Inhibitors - Wang, Min; Zhai, Xiaoyang; Li, Ji; Guan, Jingyuan; Xu, Shuhui; Li, YuYing; Zhu, Hui (Frontiers in Immunology, 2021)
Recently, the overall survival (OS) of patients with advanced cancer has been improved due to the application of immune checkpoint inhibitors (ICIs). Low response rate and high occurence of immune-related adverse events (irAEs) are the main disadvantages that limit the use of ICIs. Identification of ideal predictive biomarkers of early response and irAEs is helpful to guide treatment strategies. Most of the studies focused on the predictive role of PD-L1 and tumor mutant load（TMB). However, PD-L1 detection requires tissue samples and TMB is too expensive to suitable for dynamic detection. Cytokines are small soluble proteins with a wide range of biological activity that are secreted by activated immune cells or tumor cells and act as a bridge between innate immunity, infection, inflammation and cancer.Cytokines can be detected in peripheral blood and suitable for dynamic detection.During the era of ICIs,many studies investigated the role of cytokines in prediction of the efficiency and toxicity of ICIs.Herein, we review the relevant studies on the role of TNF-α, IFN-γ, IL-6, TGF-β and other cytokines in prediction of the ICIs-related reactions and adverse events,and explore the immunomodulatory mechanisms.Finally, the most important purpose of this review is to help identify predictors of ICI to screen patients who are most likely to benefit from immunotherapy.